2020
DOI: 10.3390/ijms21165702
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review—The Potential Implications of Different Platelet-Rich Plasma (PRP) Concentrations in Regenerative Medicine for Tissue Repair

Abstract: The number of studies evaluating platelet-rich plasma (PRP) concentration has substantially grown in the last fifteen years. A systematic review on this field has been realized by evaluating in the identified studies the in vitro PRP concentration—also analyzing the platelet amount—and the in vivo PRP effects in tissue regeneration compared to any control. The protocol has been developed in agreement with the Preferred Reporting for Items for Systematic Reviews and Meta-Analyses-Protocols (PRISMA-P) guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 58 publications
0
73
0
Order By: Relevance
“…PRP is another effective agent for wound healing because it contains abundant growth factors and other substances that can restore growth factors in diabetic wounds. The cellular processes, such as chemotaxis, cell differentiation and angiogenesis, and several target cells in wound healing were stimulated by PRP [30,31]. The antiapoptotic effect of PRP through the activation of the Bcl-2 protein and Akt signaling was a contributing factor to improve wound healing by stimulating hair growth [32].…”
Section: Discussionmentioning
confidence: 99%
“…PRP is another effective agent for wound healing because it contains abundant growth factors and other substances that can restore growth factors in diabetic wounds. The cellular processes, such as chemotaxis, cell differentiation and angiogenesis, and several target cells in wound healing were stimulated by PRP [30,31]. The antiapoptotic effect of PRP through the activation of the Bcl-2 protein and Akt signaling was a contributing factor to improve wound healing by stimulating hair growth [32].…”
Section: Discussionmentioning
confidence: 99%
“…5,8,19 The anti-apoptotic effect of PRP has been described as the most important factors stimulating hair regrowth through the Bcl-2 protein activation (anti-apoptotic regulator) and Akt signaling, improving the dermal papilla cells survival (DPCs) during the hair cycle. 20 In this study, after 3 sessions of PRP injection, patients were satisfied with improvement in form of significant increase in hair density and detection of small regrown hairs.…”
Section: Discussionmentioning
confidence: 63%
“…The anti‐apoptotic effect of PRP has been described as the most important factors stimulating hair regrowth through the Bcl‐2 protein activation (anti‐apoptotic regulator) and Akt signaling, improving the dermal papilla cells survival (DPCs) during the hair cycle 20 …”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first attempt to review comparative studies that focused on different methods for each stage of PRP processing. In the systematic review conducted by Gentile et al focusing on optimal concentration of PRP, results shown that higher concentrations of PRP may be associated with a significant decline in cell proliferation (Gentile and Garcovich, 2020b), which stresses the need for standardization of procedures in this regard. In other systematic review, recently conducted by Chahla et al (2017) studies in which PRP was used for musculoskeletal conditions were assessed in relation to the reporting of the applied methods for PRP processing or of the composition of the final product.…”
Section: Discussionmentioning
confidence: 99%